Rules of Human Conduct in War in the Light of Islamic Jurisprudence and International Humanitarian Law - Al Shamary, Abdulrazzaq (Journal of Legal Sciences, 2023)
The importance of the research lies in the description of war within the framework of international law and Islamic jurisprudence, the extent of its legality, and an attempt to highlight the legal value of the rules of human conduct in the war for which Islamic Sharia has established, and how it dealt with some categories of fighters (prisoners for example), and comparing it with the international conventions and treaties regulating this conduct in the field of international humanitarian law.      As for the research problem, it is an attempt to establish the rules of human behavior in war, which came in The Hague Conventions (1899-1907) and the Geneva Conventions of 1949 and the protocols attached to them and rooting them with the provisions and rules that came in Islamic jurisprudence that control the rhythm of that behavior, and the possibility of reconciling between Islamic law and law International humanitarian law and to highlight the uniqueness of Islamic jurisprudence.     The research concludes that many of the rules of human behavior stipulated in international treaties are derived from the spirit of Islamic jurisprudence, which was a forerunner in rooting and crystallizing the human nature of war, through its objective view of the state of war and the rules of human behavior in it, so we can say that Islamic Sharia preceded international law by many centuries, in establishing ideal rules of human behavior in war and in combat.